Development and Performance Analysis of Pneumatic Soft-Bodied Bionic Basic Execution Unit. (3rd November 2020) - Zhang, Yu; Zhao, Wenchuan; Wang, Ning; Lu, Dengyu
Abstract : This paper studies the design of pneumatic soft-bodied bionic basic execution unit with soft-rigid combination, which can be used as an actuator for pneumatic soft-bodied robots and soft-bodied manipulators. This study is inspired by structural characteristics and motion mechanism of biological muscles, combined with the nonlinear hyperelasticity of silica gel and the insertion of thin leaf spring structure in the nonretractable layer. Response surface analysis and numerical simulation algorithm are used to determine the optimal combination of structural dimension parameters by taking the maximum output bending angle of the basic executing unit as the optimization objective. Based on Odgen's third-order constitutive model, the deformation analysis model of the basic execution unit is established. The physical model of pneumatic soft-bodied bionic basic execution unit is prepared through 3D printing, shape deposition, soft lithography, and other processing methods. Finally, the motion and dynamic characteristics of the physical model are tested through experiments and result analysis, thus obtaining curves and empirical formulas describing the motion and dynamic characteristics of the basic execution unit. The relevant errors are compared with the deformation analysis model of the execution unit to verify the feasibility and effectiveness of the design of the pneumatic soft-bodied bionic basic execution unit. The above research methods, research process, and results can provide a reference for the research and implementation of pneumatic and hydraulic driven soft-bodied robots and grasping actuators of soft-bodied manipulators.